Analisis Strategi Komunikasi dalam Upaya Membangun Keharmonisan Keluarga pada Pasangan Dokter di Palemban - Rosa Carella, Thalia; Yusdi Haq (Rayah Al-Islam, 2025)
Marriage represents an important stage in a person's life. The purpose is not only at forming a family but also at creating a harmonious family. One of the key in building such harmony is an effective communication between spouses. Poor communication can lead to misunderstandings and, ultimately, relationship breakdowns. Married couples, particularly those in demanding professions such as doctors, often face challenges in maintaining effective communication due to high work demands and busy schedules. This study employs a qualitative approach using in-depth interviews with doctor couples in Palembang. The objective is to analyze and identify communication strategies used between spouses who are both medical professionals, the impact of external factors, and explore how these couples balance their roles in the family and their responsibilities as doctors. The results of this study that the communication strategies most commonly used to foster family harmony include making intentional time for communication amidst daily activities, discussing specific topics every day, and showing respect for each other's opinions. The main external influences that disrupt communication are limited time together and a lack of attention to family matters due to work commitments. To overcome these challenges, couples manage their practice schedules and share household responsibilities with their partners.